PELUANG DAN TANTANGAN PEMANFAATAN TEKNOLOGI BIG DATA UNTUK MENGINTEGRASIKAN PELAYANAN PUBLIK PEMERINTAH - Khikmatul Islah (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
Due to the Good Governance, one of the efforts made is by developing New Public Service paradigm. The implementation of this paradigm can provide service without discrimination, because all services activities carried out by the government are oriented towards providing excellent service, as well as realizing the principle of public service as stated in Law number 25 of 2009 concerning Public Service namely the principle of public interest, legal certainty, rights  equality, balance of rights and obligations, professionalism, participative, equality of treatment/non-discrimination, openness, accountability, facilities and special treatment for vulnerable group, timeliness, speed, convenience and affordability. Public service improvement shall obtain the main attention from the government, because public service is basic social rights of the community (social rights or fundamental rights). The juridical foundation of public service on the basic social rights is regulated in the provisions of Article 18 A paragraph (2) and Article 34 paragraph (3) of the 1945 Constitution. In such a way, the Constitution explicitly regulates public service as a form of basic social rights (the rights to receive). The rejection or deviation of public service is contrary to the 1945 Constitution. Therefore, related to the circumstances, the Government shall strive improving the quality of service, among other by way of service innovation by utilizing technological progress. One of the developing technologies today is Big Data technology. There are an opportunity and a challenge for the Government to use it to improve service quality.